2018
DOI: 10.17236/sat00169
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of analgesia for piglet castration under isoflurane anaesthesia with parenteral butorphanol, meloxicam or intratesticular lidocaine

Abstract: This blinded prospective study investigated analgesic effects of intramuscular (IM) butorphanol, meloxicam or intratesticular (IT) lidocaine for castration of 7-14 days old piglets under isoflurane anaesthesia. 66 piglets were randomly injected with: meloxicam IM (0.4 mg/kg; group M), butorphanol IM (0.2 mg/kg; group B), or both (group BM) 20 minutes prior to castration, or lidocaine IT (4 mg/kg (group ML4) or 8 mg/kg (group ML8)) together with meloxicam IM (0.4 mg/kg) under anaesthesia with 1.8% end-tidal iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…In addition, each event was filmed and evaluated. To assess the quality of limb movements for every piglet and event, a specific score was established based on Berchtold et al [ 20 ] and Hug et al [ 21 ]. Both front and hind limbs as well as the spine/back were assessed individually for each testicle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, each event was filmed and evaluated. To assess the quality of limb movements for every piglet and event, a specific score was established based on Berchtold et al [ 20 ] and Hug et al [ 21 ]. Both front and hind limbs as well as the spine/back were assessed individually for each testicle.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas different concentrations and application techniques of lidocaine [2,3,8,9,[15][16][17][18][19]21,39,41,[47][48][49][50][51][52][53][54][55][56] and procaine [9,17,41,42,[57][58][59] have been excessively studied in the context of piglet castration, bupivacaine was analyzed only in combination with lidocaine by Bonastre et al [60]. To the best of our knowledge, mepivacaine, an approved drug in several European countries for intraarticular and epidural injections in horses, has never been used in studies examining piglet castration.…”
Section: Plos Onementioning
confidence: 99%
“…2 However, in an earlier inhouse study that aimed at improving analgesia for castration performed under inhalation anaesthesia in piglets, it was observed that the sole use of butorphanol before induction of anaesthesia might induce adverse reactions. 6 Cyanosis, salivation, vomiting, dyspnoea, excitations and paddling were noted after drug administration in five out of seven piglets. 6 Also with inject able anaesthesia protocols containing butorphanol (ketamineazaperone-butorphanol) in piglets undergoing castration, jumping and excitations after administration of this drug mixture were observed, which could not be explained.…”
Section: Introductionmentioning
confidence: 93%
“…6 Cyanosis, salivation, vomiting, dyspnoea, excitations and paddling were noted after drug administration in five out of seven piglets. 6 Also with inject able anaesthesia protocols containing butorphanol (ketamineazaperone-butorphanol) in piglets undergoing castration, jumping and excitations after administration of this drug mixture were observed, which could not be explained. 7 To the knowledge of the authors, previous studies that used butorphanol in pigs in combination with sedatives or injectable anaesthetics 3, 5, 7, 9-12 never described the adverse effects observed by Hug et al 6 Besides some excitations during induction of anaesthesia 7, 10 that were not attributed to butorphanol, no study mentioned behavioural side effects despite using 0,2 mg/kg butorphanol, probably as a result of heavy sedation caused by other concurrently used drugs.…”
Section: Introductionmentioning
confidence: 93%
“…Butorphanol inhibits pain at the central level and should be effective to relieve acute pain even during surgery. Positive effects on behaviour during and shortly after surgical castration were observed by Courboulay et al (2015), but use of this drug was discarded by Viscardi and Turner (2018a) and Hug et al (2018) due to unacceptable side effects (e.g. vomiting, trembling, leg paddling).…”
Section: Husbandry Interventions In Suckling Piglets Painful Consequmentioning
confidence: 99%